The nursing work at emergency of the Antônio Pedro University Hospital - Machado, Simone Cruz (Online Brazilian Journal of Nursing, 2004)
The aim of this research are the strategies used  by nursing team to face work conditions at Emergency Services of the Antônio Pedro University Hospital of Federal Fluminense University. This research was carried out focused at the emergency working quotidian  manifestations that were understood in a context of a continuous changing process. In this study,  we have searched to characterize the nursing work at emergency as a whole, describing their objects, instruments and activities and their articulation with working team process. In this movement, have learned the nursing team conception about their own activities. The working conditions analysis have reflected nursing work specific aspects as well as the attending dynamic at emergency, considering the political and social content and the progressive deterioration of the health care. Finally, have discussed the ethical and political implications of nursing team daily practices, where their memberships developing strategies to dare the difficulties of their work process with the available resources.